The negotiation trap: An experiment on a large language model - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2024)
In an experiment on the large language model GPT-4o, a supplier always makes a higher profit if it replaces uniform contract terms with a set of terms between which the customer may choose. The extra profit results from price discrimination. There is a first order and a second order effect. The first order effect results from heterogeneous willingness to pay for a more protective term. The second order effect results from the possibility that contract choice is a signal for general willingness to pay for the traded commodity. In the experiment, the effect is bigger if the least protective version is labelled as the default, and more protective terms as an "upgrade". The effect is smaller if, conversely, the most protective version is labelled as the default and less protective (and cheaper) versions as an opportunity for "savings". The effect is also bigger if the supplier only sets the price after it knows which version of the contract the consumer chooses. The profit increasing effect of giving the consumer a choice is strong. There is no piece of demographic information that has a stronger effect. Most pieces of demographic information (which the supplier might, for instance, learn through cookie data) have a significantly smaller effect on profit. If the supplier combines cookie information about demographic markers with contract choice, it always makes an extra profit.
hdl:21.11116/0000-0010-5EC1-B
Keywords: C91; D01; D02; D12; D42; D91; K12; 330; forced choice of contract clause; price discrimination; large language model; experiment